Leaf trichomes identification in lamiaceae family plants and contribution to high school biology learning - Yesi Tri Agustin; Ermayanti Ermayanti; Rahmi Susanti (STKIP Persada Khatulistiwa Sintang, 2022)
Many trichomes in plant organs have been studied previously, but research on leaf trichomes in several plants in the Lamiaceae tribe has never been studied before. The research has been conducted at the Laboratory of FKIP Palembang. This study using a descriptive method. The plants used in this study were from the Lamiaceae family, such as Ocimum sanctum, Penorema canescens, Salvia splendens, Lavandula angustifolia, Hyptis rhomboides, Anisomeles indica, and Clerodendrum japonicum. Observations using a binocular microscope at magnifications of 40, 100, and 400. This study was conducted by observing the type of trichome, the number of trichome cell arrangement, the shape of the trichome, and the size of the trichome. The results showed that in the Lamiaceae tribe there were glandular trichomes and non-glandular trichomes. The number of trichome cell arrangement consists of unicellular and multicellular trichomes. The longest average trichome size ranged from 89.5 microns and the shortest average ranged from 8.7 microns. The results are used as basic data in the anatomical structure of the trichomes of the Lamiaceae tribe and as learning enrichment material for KD 3.3 and KD 4.3 in the form of booklets.